2022
DOI: 10.1192/bjp.2022.160
|View full text |Cite
|
Sign up to set email alerts
|

Association between polypharmacy and depression relapse in individuals with comorbid depression and type 2 diabetes: a UK electronic health record study

Abstract: Background Individuals with physical comorbidities and polypharmacy may be at higher risk of depression relapse, however, they are not included in the ‘high risk of relapse’ group for whom longer antidepressant treatment durations are recommended. Aims In individuals with comorbid depression and type 2 diabetes (T2DM), we aimed to investigate the association and interaction between depression relapse and (a) polypharmacy, (b) previous duration of antidepressant treatment. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Antidepressants are also known to cause cardiac symptoms, which may be of concern to people with a condition such as type 2 diabetes, which can lead to cardiovascular disease. Although antidepressants were shown to improve glycaemic control in a systematic review of RCTs, they have also been shown in observational studies to be associated with hyperglycaemia (24) and starting insulin (25), as well as hypoglycaemia (26) (though all these may have been subject to confounding by indication). Despite the need to successfully treat depression in order effectively manage physical health in type 2 diabetes, without clear evidence on the benefits and harms of antidepressant medication in this patient group, and accompanying treatment guidelines, it is understandable that clinicians may be wary to prescribe.…”
Section: Discussionmentioning
confidence: 99%
“…Antidepressants are also known to cause cardiac symptoms, which may be of concern to people with a condition such as type 2 diabetes, which can lead to cardiovascular disease. Although antidepressants were shown to improve glycaemic control in a systematic review of RCTs, they have also been shown in observational studies to be associated with hyperglycaemia (24) and starting insulin (25), as well as hypoglycaemia (26) (though all these may have been subject to confounding by indication). Despite the need to successfully treat depression in order effectively manage physical health in type 2 diabetes, without clear evidence on the benefits and harms of antidepressant medication in this patient group, and accompanying treatment guidelines, it is understandable that clinicians may be wary to prescribe.…”
Section: Discussionmentioning
confidence: 99%
“…Such situations often arise in cases where patients present with multiple comorbidities requiring treatment from different therapeutic classes, or when monotherapy does not yield the desired clinical improvement. Consequently, deprescribing may not always be an appropriate strategy [21].…”
Section: Maintaining a Balancementioning
confidence: 99%